Contrasting State‐Dependent Effects of Natural Forcing on Global and Local Climate Variability - Ellerhoff, Beatrice; Kirschner, Moritz J.; Ziegler, Elisa; Holloway, Max D.; Sime, Louise; Rehfeld, Kira; Ellerhoff, Beatrice; 1 Department of Geosciences and Department of Physics Tübingen University Tübingen Germany; Kirschner, Moritz J.; 2 Institute of Environmental Physics Heidelberg University Heidelberg Germany; Ziegler, Elisa; 1 Department of Geosciences and Department of Physics Tübingen University Tübingen Germany; Holloway, Max D.; 3 Scottish Association for Marine Science Oban UK; Sime, Louise; 4 British Antarctic Survey Cambridge UK (Geophysical Research Letters, 2022)
Natural forcing from solar and volcanic activity contributes significantly to climate variability. The post‐eruption cooling of strong volcanic eruptions was hypothesized to have led to millennial‐scale variability during Glacials. Cooling induced by volcanic eruption is potentially weaker in the warmer climate. The underlying question is whether the climatic response to natural forcing is state‐dependent. Here, we quantify the response to natural forcing under Last Glacial and Pre‐Industrial conditions in an ensemble of climate model simulations. We evaluate internal and forced variability on annual to multicentennial scales. The global temperature response reveals no state dependency. Small local differences result mainly from state‐dependent sea ice changes. Variability in forced simulations matches paleoclimate reconstructions significantly better than in unforced scenarios. Considering natural forcing is therefore important for model‐data comparison and future projections. Plain Language Summary: Climate variability describes the spatial and temporal variations of Earth's climate. Understanding these variations is important for estimating the occurrence of extreme climate events such as droughts. Yet, it is unclear whether climate variability depends on the mean surface temperature of the Earth or not. Here, we investigate the effects of natural forcing from volcanic eruptions and solar activity changes on climate variability. We compare simulations of a past (cold) and present (warm) climate with and without volcanism and solar changes. We find that overall, the climate system responds similarly to natural forcing in the cold and warm state. Small local differences mainly occur where ice can form. To evaluate the simulated variability, we use data from paleoclimate archives, including trees, ice‐cores, and marine sediments. Climate variability from forced simulations agrees better with the temperature variability obtained from data. Natural forcing is therefore critical for reliable simulation of ...